2019
DOI: 10.1016/j.neuropharm.2018.03.020
|View full text |Cite
|
Sign up to set email alerts
|

N-Oleoyl-glycine reduces nicotine reward and withdrawal in mice

Abstract: Cigarette smokers with brain damage involving the insular cortex display cessation of tobacco smoking, suggesting that this region may contribute to nicotine addiction. In the present study, we speculated that molecules in the insular cortex that are sensitive to experimental traumatic brain injury (TBI) in mice might provide leads to ameliorate nicotine addiction. Using targeted lipidomics, we found that TBI elicited substantial increases of a largely uncharacterized lipid, N-acyl-glycine, N-oleoyl-glycine (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 61 publications
3
56
1
Order By: Relevance
“…One such effector gene family (Cbeg12) encodes for the production of N-acyl-3-hydroxypalmitoyl-glycine (commendamide), which was also found in culture from Bacteroides vulgatus that harbors a gene highly similar to Cbeg12 [99]. Commendamide resembles long-chain N-acyl-amino acids that function as mammalian signaling molecules through activation of GPCRs or PPARs, such as N-oleoyl-glycine [100], and was found to activate GPCR G2A/GPR132, which has been implicated in autoimmunity and atherosclerosis [99]. More recently, the same authors, by again using bioinformatic approaches, found that some commensal bacteria can produce other N-acyl-amides as well as complex long-chain fatty acids capable of activating the same GPCRs as their host counterparts and, in some cases, GPR119, that belongs to the eCBome [101,102].…”
Section: Endocannabinoid-like Molecules (Long-chain N-acyl-amides)mentioning
confidence: 99%
“…One such effector gene family (Cbeg12) encodes for the production of N-acyl-3-hydroxypalmitoyl-glycine (commendamide), which was also found in culture from Bacteroides vulgatus that harbors a gene highly similar to Cbeg12 [99]. Commendamide resembles long-chain N-acyl-amino acids that function as mammalian signaling molecules through activation of GPCRs or PPARs, such as N-oleoyl-glycine [100], and was found to activate GPCR G2A/GPR132, which has been implicated in autoimmunity and atherosclerosis [99]. More recently, the same authors, by again using bioinformatic approaches, found that some commensal bacteria can produce other N-acyl-amides as well as complex long-chain fatty acids capable of activating the same GPCRs as their host counterparts and, in some cases, GPR119, that belongs to the eCBome [101,102].…”
Section: Endocannabinoid-like Molecules (Long-chain N-acyl-amides)mentioning
confidence: 99%
“…Although the functional activities of NOleGly are still largely unknown, its predominant role in the regulation of behavioral actions, such as body temperature and motor activity, in the control of physiological processes, such as energy homeostasis and food, has been recently reported [52,54,55]. NOleGly ameliorated withdrawal-associated behaviors and prevented nicotine addiction in vivo [56]. The anti-reward effect, assessed in the conditioned place preference (CPP) paradigm, required PPAR-α activation as was reverted by PPAR-α antagonist administration [56].…”
Section: N-acyl Glycinesmentioning
confidence: 99%
“…NOleGly ameliorated withdrawal-associated behaviors and prevented nicotine addiction in vivo [56]. The anti-reward effect, assessed in the conditioned place preference (CPP) paradigm, required PPAR-α activation as was reverted by PPAR-α antagonist administration [56]. Moreover, the capability of NOleGly to interfere with the aversive properties associated with acute naloxone-precipitated morphine withdrawal (MWD) and the rewarding effects of morphine in Sprague-Dawley rats has been investigated [57].…”
Section: N-acyl Glycinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among NAEs, the cannabinoid agonist AEA binds to CB1 and CB2 receptors and transient receptor potential vanilloid type 1 (TRPV1) at physiologically relevant concentrations, the others display an affinity for peroxisome proliferator-activated receptor-α (PPARα; Lo Verme et al, 2005 ; Hansen, 2010 ; Petrosino et al, 2010 ; Pistis and Muntoni, 2017 ), G protein-coupled receptors such as GPR55 (Baker et al, 2006 ) and GPR119, and TRPV1 (Piomelli, 2013 ). N- acyl amino acids are less characterized; however, evidence suggests a role for GPR18, GPR55, and GPR92, and PPARα in mediating some of the actions of N- oleoylglycine (Burstein, 2018 ; Donvito et al, 2019 ), which is one of the most studied among these molecules.…”
Section: Introductionmentioning
confidence: 99%